APLIKASI PRAKSIS MODEL TPR DALAM PEMEROLEHAN BAHASA INGGRIS ANAK USIA DINI - Yeyen Yuniarti (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2013)
The importance of knowing a suitable teaching method and a process of first language acquisition could help the early learners of second language to acquire and explore an English language in kindergardens. Actually, first language acquisition needs interaction to communicate naturally by gradual phases based on the early child’s cognitive level and language system such as syntaxes, fonetics, morphology and pragmatics by doing imitation of the utterances. Based on the experts on how the children learn first language, the acquisition of first language comes through listening and speaking. So, in learning second language is also focused on listening initially, then speaking. Therefore, the suitable method of learning English language is Total Physical Response (TPR). TPR adopts learners to listen and speak first by using command in verbal, speech and action where the learners will imitate to reproduce words as what teacher says, and the learners like to act everywhere because early learners has a limited attention span. TPR is a fun model to avoid learners’ boredness and to give motivation. Finally, the teacher has an important role as an active actor. Keywords: acquisition, Total Physical Response (TPR)